Case Report: Identification of Germline Chimerism in Monochorionic Dizygotic Twins - Chen, Juan; Xu, Jian; Chen, Zhi-Heng; Yin, Min-Na; Guo, Xin-Yu; Sun, Ling (Frontiers in Genetics, 2021)
Monochorionic twins are generally considered to be monozygotic, as monochorionic dizygotic (MCDZ) twins are extremely rare in natural pregnancies. Several studies have reported this rare occurrence, and most of these pregnancies have been conceived by assisted reproductive technology (ART). These reports mostly focused on MCDZ twin pregnancies and the childhood development of the twins; a follow-up into adulthood and the effect on their reproduction has not been reported. In this case study, we report a case of chimerism in opposite-sex MCDZ twins who were naturally conceived and have reached reproductive maturity. We collected oral mucosal, endometrial, and germ cells from the twins and evaluated their chimerism using single-nucleotide polymorphism (SNP) array and Droplet Digital PCR (ddPCR). The SNP array showed that they had 4,049 non-allele shared loci, and they inherited nearly 50% informative SNP loci from each parent, confirming that they are dizygotic twins. We found that the female twin had a 46, XX (2)/46, XY (78) karyotype in her peripheral blood. The SNP array confirmed that the female twin and male twin had the same blood haplotype. The ddPCR result showed 92.84 (±1.80%) chimerism in her blood. In case of chimerism in her germline, the female twin chose preimplantation genetic testing for aneuploidy for her blastocysts. Fortunately, the patient only had blood chimerism. A healthy boy was born at 39 weeks of gestation.